Synthesis of multiwall carbon nanotube with fly ash in the production of desired green concrete - Jumaat A.A.; Afandi N.F.; Manap A.; Zainuddin R.A.; Mahalingam S.; Abd Kadir N.F. (Institute of Physics Publishing, 2023)
Ashes; Compressive strength; Curing; Fly ash; Industrial research; Industrial waste disposal; Multiwalled carbon nanotubes (MWCN); Concrete productions; Curing process; Green concrete; Concrete products